The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.memsci.2016.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Aging of polymers of intrinsic microporosity tracked by methanol vapour permeation

Abstract: The initially very promising transport properties of glassy high free volume polymers deteriorate rapidly over time. In this work, we focused on this aging phenomenon in two polymers of intrinsic microporosity (PIMs), namely PIM-1 and PIM-EA-TB. To identify the main mechanisms involved, we studied the time-declines of permeability and diffusivity of methanol vapours in flat membranes with approximately equal thicknesses. The permeation measurements were carried out using a continuous flow permeation method wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…[34] Glassy polymers such as PIM-1 are intrinsically non-equilibrium materials and are known to lose free volume over time, owing to slow rearrangements in the packing of the polymer chains. This physical aging [35] was found to be the primary cause of the well-established decay in permeability of PIM-1 membranes over time. [36] Interestingly, aging of the polymer was found to impact not only its permeability, but also to enhance its selectivity, [37] which is a critical parameter when evaluating the performance of polymer-based membranes.…”
Section: Introductionmentioning
confidence: 95%
“…[34] Glassy polymers such as PIM-1 are intrinsically non-equilibrium materials and are known to lose free volume over time, owing to slow rearrangements in the packing of the polymer chains. This physical aging [35] was found to be the primary cause of the well-established decay in permeability of PIM-1 membranes over time. [36] Interestingly, aging of the polymer was found to impact not only its permeability, but also to enhance its selectivity, [37] which is a critical parameter when evaluating the performance of polymer-based membranes.…”
Section: Introductionmentioning
confidence: 95%
“…26 It was also previously discovered that aging rate correlates strongly to the T g of the polymer 27 and that T g increases with physical aging. 28 Although physical aging occurs without any external influence, its rate is found to be dependent on several factors, such as temperature, [29][30][31][32] gas environment, [33][34][35] and polymer structure. 33,36 More importantly, it was observed that physical aging occurs more rapidly in a thin polymer film (i.e.…”
Section: Physical Aging In Glassy Polymersmentioning
confidence: 99%
“…Methanol treatment has been shown previously to reverse the effects of physical ageing for glassy ultra-permeable polymers and it also removes the last residues of casting solvent. 16,39,40 In addition, methanol treatment allows a direct comparison between the gas permeabilities of different polymers prior to ageing. The equivalent data for a freshly methanol treated lm of PIM-1 of similar thickness, measured under identical conditions to those of the PIM-SBFs, are also provided in Table 2 /CH 4 gas pairs and can be directly ascribed to the greater rigidity of the SBF units as compared to SBI units of PIM-1.…”
Section: Gas Permeabilitymentioning
confidence: 99%